2018
DOI: 10.18632/oncotarget.25443
|View full text |Cite
|
Sign up to set email alerts
|

Distinct age-associated molecular profiles in acute myeloid leukemia defined by comprehensive clinical genomic profiling

Abstract: Large scale comprehensive genomic profiling (CGP) has led to an improved understanding of oncogenic mutations in acute myeloid leukemia (AML), as well as identification of alterations that can serve as targets for potential therapeutic intervention. We sought to gain insight into age-associated variants in AML through comparison of extensive DNA and RNA-based GP results from pediatric and adult AML. Sequencing of 932 AML specimens (179 pediatric (age 0–18), 753 adult (age ≥ 19)) from diagnostic, relapsed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…The involvement of BCOR alterations in clonal disorders of myeloid lineage (Table 2) has been assessed primarily for myelodysplasias [83,87,91–93] and acute myeloid leukemia (AML) [94,102–104], with cases ranging from less than 1–10% in unselected cohorts. By analyzing these and other cohort studies, it was possible to identify clinical contexts where the presence of BCOR alterations is most frequent.…”
Section: Hemolymphopoietic System Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of BCOR alterations in clonal disorders of myeloid lineage (Table 2) has been assessed primarily for myelodysplasias [83,87,91–93] and acute myeloid leukemia (AML) [94,102–104], with cases ranging from less than 1–10% in unselected cohorts. By analyzing these and other cohort studies, it was possible to identify clinical contexts where the presence of BCOR alterations is most frequent.…”
Section: Hemolymphopoietic System Neoplasmsmentioning
confidence: 99%
“…By analyzing these and other cohort studies, it was possible to identify clinical contexts where the presence of BCOR alterations is most frequent. Particularly in AML, it is clear that the frequency of BCOR mutations is significantly higher in older patients than in pediatric ones [90,94,96,101], with pediatric AMLs with normal karyotype as the exception [88] and higher in secondary AML with respect to primary AML [102]. NGS techniques allow for the identification of new molecular subgroups potentially related to specific clinical characteristics, in addition to those already identifiable by cytogenetic studies.…”
Section: Hemolymphopoietic System Neoplasmsmentioning
confidence: 99%
“…A second way to improve the assessment of MRD in pediatric AML is to include RT-PCR in more patients, by the identification of more targets for RT-PCR. Large-scale genomic profiling showed that certain structural variants are highly present in pediatric AML cohorts [31]. Quantitative RT-PCR will enable a higher sensitivity of MRD assessment than flowcytometry (up to 10 −6 and 10 −4 , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In other cancers, younger age is associated with particular genetic alterations, which are considered to be "driver" genes. [33][34][35][36][37][38] We speculated that ATLL in younger patients would exhibit distinct genetic alterations and, accordingly, performed genomic analysis. We identified eight patients with ATLL who were <50 years of age at the time of diagnosis and defined them as young ATLL.…”
Section: G Enomi C L Andsc Ape Of Atll In Young Er Individual Smentioning
confidence: 99%